Statistical Power in Three-Arm Cluster Randomized Trials. (December 2014) - Liu, Xiaofeng Steven
This article shows how to compute statistical power for testing the main effect of treatment in three-arm cluster randomized trials. Using orthogonal coding, we derive the exact test statistic of the treatment effect and its non-central distribution. The non-centrality parameter in the omnibus test is found to be related to the non-centrality parameters in the contrast tests. A study of physician and pharmacist comanagement of patients' blood pressure is used as an example to show the power computation in a three-arm cluster randomized trial.